The Basement Membrane Underlying the Vascular Endothelium Is Not Thrombogenic: In Vivo and In Vitro Studies with Rabbit and Human Tissue - Buchanan, M R; Richardson, M; Haas, T A; Hirsh, J; Madri, J A (Thrombosis and Haemostasis, 1987)
Studies examining the interaction of platelets with exposed subendothelium in vivo have reported conflicting results, lo examine possible explanations for the apparently discrepant findings, we measured the platelet reactivity of subendothelium prepared by a number of methods both in vivo and in vitro. In addition, we examined the possibility that 13-hydroxyoc-tadecadinoic acid (13-HODE), an endothelial cell-derived chemorepellant, modulates the reactivity of the subendothelium to platelets. In vivo, the subendothelium of segments of rabbit carotid arteries was exposed by removing the endothelial cells by air perfusion or by balloon catheter stripping. Platelet accumulation onto the dc-cndothelialized segments was assessed by 3H-radioaclivily uptake, using 3H-adenine-labelled platelets, and by scanning electron microscopy. In vitro, 3H-adenine-labelled platelet adhesion was measured onto plain plastic discs and onto plastic discs coated with the following purified basement membrane components: collagens type I, III, IV, V, laminin, or fibronectin. In addition, 3H-adenine-labelled platelet adhesion was measured onto plastic discs coveredwith human endothelial cells or onto the basement membrane underlying the endothelial cells.In vivo, there was marked 3H-platelet accumulation onto the ballon catheter carotid arteries one hour after injury. In contrast, there was no platelet accumulation onto the subendothelium of carotid arteries de-endothelialized by air perfusion. These differences were confirmed by scanning electron microscopy. Transmission electron microscopic examination demonstrated that the extracellular matrix was intact following the air perfusion injury whereas the majority of it was removed by the balloon catheter injury.In vitro, the accumulation of 3H-platelets onto plain discs and onto discs coated with any of the four collagens, fibronectin or laminin was significantly greater than the adhesion of 3H-platelets onto intact endothelial cells or the basement membrane prepared by cellulose acetate stripping. In contrast, 3H-platelet adhesion onto the basement membrane prepared by ammonium hydroxide treatment was significantly increased. An HPLC analysis of methanol extracts obtained from the two basement membranes and the cultured endothelial in vitro demonstrated that there was significant amounts of 13-HODE present in the endothelial cells and in the basement membrane prepared by the mechanical stripping, but there was no detectable 13-HODE in the basement membrane prepared by ammonium hydroxide treatment.We conclude that platelets do not adhere to subendothelium immediately beneath the endothelium and that this thromboresistance is contributed to by 13-HODE. We also suggest that the observed thrombogeneicity of subendothelium following balloon-induced injury is due to the mechanical removal of sub-endothelial structures including 13-HODE, exposing deeper more thrombogenic vascular wall structures.
Keywords: Basement membrane; 13-hydroxy-octadecadienoic acid (13-HODE); Vascular thromboresistance